Selection of optimization objectives for decision-making in building energy retrofits - Jafari, Amirhosein; Valentin, Vanessa (Building and environment, 2018)
Building energy retrofitting has emerged as a primary strategy for reducing energy use and carbon emissions. The decision about which retrofit measures should be implemented in a particular project is a single- or multi-objective optimization problem subject to many constraints and limitations. Different objective(s) have been used in the literature, however the identification and selection of the objective(s) for this optimization problem is still a challenge. This study develops a decision matrix that guides decision-makers on how to select the objective(s) for a single- or multi-objective optimization problem that results in the selection of the best energy retrofitting strategy, by considering and defining the “investor benefits” term, the type of potential investors, and the type of potential benefits of building energy retrofits. Four types of investors are considered in this study: owner-occupant, absent owner, leaser, and external investor. In addition, a case study is used to illustrate how different types of investors may affect the selection of objective functions and, therefore, the final decisions for optimum energy retrofits. Results show that when the investor is the owner-occupant, a higher investment is suggested for energy retrofits to achieve optimum benefits. •The investor benefits has been neglected on decision making for energy retrofits.•A decision matrix that guides on how to select the objective function(s) is proposed.•The matrix relates energy retrofitting benefits to identified potential investors.•A higher energy retrofitting investment is suggested for owner-occupant investor.